2006
DOI: 10.1152/ajprenal.00112.2005
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous 5′-nucleotidase improves glomerular autoregulation in Thy-1 nephritic rats

Abstract: Experiments were performed to characterize renal hemodynamics in Thy-1 nephritic rats. A monoclonal antibody against Thy-1 was intravenously injected to induce mesangiolysis in rats, and 2 days later renal hemodynamic responses to variations in blood pressure were determined. In the first series of experiments, autoregulation of renal plasma flow (RPF) or glomerular filtration rate (GFR) was impaired in nephritic rats. In response to a reduction in blood pressure (98 Ϯ 2 to 80 Ϯ 1 mmHg), both RPF (4.17 Ϯ 0.63 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 46 publications
4
25
0
Order By: Relevance
“…Thus, hyperglycaemia by itself would reduce afferent arteriolar tone by attenuating TGFback tone [20]. Previous findings have indicated that most of autoregulatory tone comes from TGFback in the range of arterial pressure between 100 and 80 mmHg under our experimental condition [5,11,12]. Consistent with the above hypothesis, the present data indicate that renal autoregulation was markedly impaired in ZDF rats at spontaneous levels of mean BP, reducing preglomerular vascular tone and participating in glomerular hyperfiltration.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Thus, hyperglycaemia by itself would reduce afferent arteriolar tone by attenuating TGFback tone [20]. Previous findings have indicated that most of autoregulatory tone comes from TGFback in the range of arterial pressure between 100 and 80 mmHg under our experimental condition [5,11,12]. Consistent with the above hypothesis, the present data indicate that renal autoregulation was markedly impaired in ZDF rats at spontaneous levels of mean BP, reducing preglomerular vascular tone and participating in glomerular hyperfiltration.…”
Section: Discussionsupporting
confidence: 90%
“…Animal preparations were performed, as detailed previously [5,11,12,29] and in ESM, Haemodynamics. Under anaesthesia, the right jugular vein was cannulated with polyethylene tubing (PE50).…”
Section: Haemodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because PGE 2 is an important mediator of inflammation, this may represent a vicious circle mechanism to drive PGE 2 -induced inflammatory events in the kidney cortex interstitium. However, data published only recently indicate that prostanoids maintain renal circulation in (Thy-1)-nephritis (49). If so, then inhibition of prostanoid secretion by prostanoids (e.g., PGE 2 ) would prevent a prostanoid washout and thus would be involved in maintaining renal circulation during nephritis, at least in rats.…”
Section: Discussionmentioning
confidence: 99%
“…There are significant pro-inflammatory activities of extracellular nucleotides during anti-Thy-1 nephritis, and an anti-inflammatory role for glomerular ecto-nucleotidases suggested to convert ATP and ADP into anti-inflammatory adenosine [292]. Tuboglomerular feedback is diminished in Thy-1 nephritic rats, but this is improved by exogenous 5′-nucleotidase [363].…”
Section: Nephritismentioning
confidence: 99%